A current assessment on the production of bacterial keratinases. (December 2014) - Daroit, Daniel Joner; Brandelli, Adriano
Abstract Keratinolytic proteases are microbial enzymes that hydrolyze keratins, recalcitrant proteins found in the epidermis and epidermal appendages of vertebrates. Keratin-rich materials are abundantly generated as wastes from agroindustrial activities, particularly the meat and poultry industries. Therefore, these enzymes are postulated for several applications, including the bioconversion of keratin-rich materials, utilization as animal feed supplements, action as de-hairing agents in tannery, prion degradation, among others. Consequently, production of keratinases in sufficient amounts is necessary to meet industrial and commercial demands. This manuscript presents an overview regarding the sources of keratinases, emphasizing general aspects and mechanisms, such as substrate induction and catabolite repression, controlling keratinase synthesis by Bacillus species. The current research status and main approaches employed to obtain keratinases are discussed in a biotechnological perspective, highlighting the role of keratin-rich wastes as growth substrates, the use of mathematical models to optimize keratinase yield and also investigations on the heterologous expression of keratinases.